Reversible defect engineering in graphene grain boundaries - Krishna Balasubramanian (Nature Portfolio, 2019)
Engineering the grain boundary size of chemical vapor deposited monolayer graphene can reversibly tune its electronic properties. Here, the authors report a thermodynamic correlation for 100 μm long channels in graphene by reversibly changing its electronic mobilities from 1,000 to 20,000 cm2 V−1 s−1.